2001
DOI: 10.1046/j.1365-2168.2001.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of benign lesions in patients resected for suspicious hilar obstruction

Abstract: Because of the limitations of current diagnostic tools, a false-positive preoperative diagnosis of malignancy resulted in a 15 per cent resection rate of benign lesions in this series of suspicious hilar strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(125 citation statements)
references
References 6 publications
4
110
1
10
Order By: Relevance
“…In the present study, the rate of patients (15%) with benign lesions misdiagnosed as malignancy was similar to the rate (15%) observed in a previous study performed at our center a decade earlier (1983-1997) [16] . Despite considerable improvements in imaging techniques (contrast enhanced multi-slice CT and MRC), and an increase in the number of imaging procedures (a mean of 3 modalities in comparison to 2 in the previous study), patients still required unnecessary extensive resections, for achieving adequate biliary drainage.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In the present study, the rate of patients (15%) with benign lesions misdiagnosed as malignancy was similar to the rate (15%) observed in a previous study performed at our center a decade earlier (1983-1997) [16] . Despite considerable improvements in imaging techniques (contrast enhanced multi-slice CT and MRC), and an increase in the number of imaging procedures (a mean of 3 modalities in comparison to 2 in the previous study), patients still required unnecessary extensive resections, for achieving adequate biliary drainage.…”
Section: Discussionsupporting
confidence: 75%
“…However, the non-HCCA patients in this series comprised of benign and malignant diseases (for instance gallbladder cancer), which makes any conclusions difficult to interpret. In a previous series of 132 patients who had undergone surgical treatment for suspicious HCCA at our center from 1983 to 1998, 15% (20/132) of the patients had benign lesions [16] . In the present study, which covers a more recent period during which improved imaging techniques were used, the rate of mis-diagnosed benign lesions was reexamined and the diagnostic features of benign and malignant lesions was compared.…”
Section: Jj Et Al Differentiation Of Proximal Bile Duct Strictures mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these histopathologic examinations yield low sensitivity, and non-diagnostic cytology or biopsy results may not rule out cholangiocarcinoma in the presence of appropriate radiologic findings [79,80] . In the absence of other explainable causes of biliary strictures, patients should be assumed to have cancer and operated on as such, accepting that 10% to 15% might prove to have a benign lesion on the final histologic investigation [81,82] . Fukuda et al [83] reported 100% sensitivity of bile duct biopsy by adding choledochoscopy to ERC, and a new technology such as SpyGlass ® , which is currently under investigation, may soon improve the diagnostic accuracy of preoperative malignancy confirmation [84,85] .…”
Section: Duct Cancermentioning
confidence: 99%
“…Imaging findings representative of this disease include biliary stricture associated with dilatation of the peripheral bile duct and lymph node enlargement. Certain patients have undergone surgical treatment for preoperative diagnosis of cholangiocarcinoma, which was finally diagnosed as a benign condition (10).…”
Section: Introductionmentioning
confidence: 99%